Zdravljenje stresne urinske inkontinence z matičnimi celicami - vizija prihodnosti? - Lukanovič, Adolf (Zdravniški vestnik, 2009)
For one third of all women urinary incontinence is a health problem. Different strategies of treatment have been used, namely surgical, medical and physiotherapy. To this armamentarium a new method - adult stem cells therapy -has been added. The source of adult autologues multipotent stem cells consists of muscle-derived stem cells, adipose-derived stem cells and mesenchymed bone marrow cells. In facilities for stem cells with processing and in the presence of specific inducing factors, muscle derived stem cells can be differentiated to striated or smooth muscles. Clinical work is based on animal models that with immunohistochemical analysis demonstrated new skeletal-muscle fiber formation at the site of injection of stem cells. In stress urinary incontinence (SUI) autologues bioptic material is obtained by using a musle needle biopsy device. From the biopsy speciment with dissociation muscle-derived stem cells are isolated and injected under local anaesthesia in the middle urethra and/or external urethral sphincter. Initial results of SUI treatment with adult muscle-derived stem cells suggest that perspectives of this method are encouraging. Stem cell therapy is promising to become minimally invasive method for reconstruction of the muscles and connective tissue of urethra and external urethral sphincter.
Keywords: matične celice; rekonstrukcija; therapy; urinska inkontinenca; zdravljenje